59 IMPROVED OUTCOMES WITH DELAYED ADMISSION TO POST-ACUTE CARE: RESULTS OF A NATURAL EXPERIMENT. (18th November 2021) - McGettigan, S; Farrell, A; Murphy, R; MacGearailt, C; O'Keeffe, S; Mulkerrin, E
Abstract: Background: In Ireland, the national Health Service Executive developed a post-acute care (PAC) scheme in 2016 to provide funds to acute hospitals for beds in nursing homes to allow discharge of patients who would benefit from a period of recovery in a nursing home before returning home when medically fit for discharge with no need for rehabilitation or long-term care (LTC). However, budgetary restrictions introduced from June 2019 resulted in a delay in access to funding. This change in funding was used as a natural experiment of the effectiveness of this scheme in a single large general hospital before and after delays due to funding restrictions. Methods: Data regarding PAC admissions for those aged 65 years or more from July to October 2017, when there were no budgetary restrictions, and from July to October 2019, when funding was delayed, were compared. Chi-square tests were used to compare proportions, and the nonparametric Mann–Whitney U test was used to compare continuous data. Results: Compared with the 2017 cohort, those in 2019 spent 6 days longer in the acute hospital following a delay in 2019 between being approved clinically as needing PAC and subsequent admission to a facility. However, readmissions to hospital within 90 days of discharge and directly from PAC were significantly higher in 2017, as was discharge from PAC directly to LTC. Conclusion: This retrospective study demonstrates restrictive practices regarding discharge to PAC introduced for budgetary reasons caused longer acute bed LOS with reduced LOS in PAC, reduced hospital RAR and reduced admissions to LTC suggesting that a pre-existing liberal selection process may result in poorer identification of appropriate patients for PAC.